The Italian State's Active Support for the Aeronautical Industry: The Case of the Caproni Group, 1910–1951. Issue 2 (2021) - Fauri, Francesca
Abstract : Based on Italian and foreign archival sources, this study shows how Italy's active assistance to its industrial apparatus soon included the newly born aircraft industry, including the Caproni Group. However, after World War II the Group went bankrupt along with most aircraft manufacturers. The suspension of aircraft development, the preference for importing allied (American and British) aircraft for civil airlines, and the denial of international assistance were the ensuing political and economic costs of defeat. In the end, Italy nationalized what was left of its aviation firms. Also, nationalization was consistent with its industrial history and represented the only way to help this sector survive.